(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Together with the constant increase in the life expectancy and standard of living of people, millions of children are growing up, and the generation of educated women is trying to fully understand the processes that take place in their organism. Women are realizing all the information about these physiological processes and how this affects their life and health. Menopause is the turning period of the climacteric period, or it happens when a certain period, a specific stage in a woman’s life, the function of the ovaries gradually disappears. The climacteric period is a physiological period in a woman’s life, but her pathological course is also possible, then it is called climacteric syndrome (CS). CS is one of the very common concepts among modern women.